Analisis Brand Switching Produk Minuman Boba di Lingkungan Kampus Udayana Bukit Jimbaran - Zendrato, Jocelyn Natania; Sadyasmara , Cokorda Anom Bayu; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Boba drinks have become very popular among young people since 2019. This study aims to determine the characteristics of consumers of boba drink products, especially students of Udayana University in Bukit Jimbaran, to analyze brand switching from several boba drink brands over the next five years, and to determine the long-term market share balance of these boba drink brands. This research was conducted through direct surveys at Chatime, Xiboba, and Mixue in Bukit Jimbaran. The sample was determined using purposive sampling method, data collection was conducted through questionnaires, and the sample size was calculated using Lemeshow’s formula amounting to 100 respondents. The data analysis method was performed using the Markov Chain method with the assistance of POM-QM software. The results indicate that the characteristics of respondents consuming boba drink products are predominantly females aged 18-24 years, with monthly spending on snacks ranging between IDR 100,000 – IDR 299,000, and an average boba drink consumption of once a month. Respondents obtain information about boba drink brands through social media and purchase boba products spontaneously without prior planning based on their own initiative. The market share of boba drink products in the first period was led by Chatime, with a market share of 47%, followed by Mixue (41%), and Xiboba (12%). In the second period, Chatime increased to 47,2%, Mixue (43,6%) and Xiboba decreased to 9,21%. In the third period and beyond, changes in market share occurred among the brands, and by the fifth period, Chatime’s market share increased to 48,6%, while Xiboba secreased to 9,46% and Mixue (41,9%). The equilibrium point is predicted to be reached in the fifth period, with Chatime holding a market share of 48,6%, Xiboba (9,5%), and Mixue (41,9%).